Benchmarking iSALE and CTH Shock Physics Codes to In Situ High‐Velocity Impact Experiments Into Fe‐Ni Targets. Issue 8 (11th August 2022) - Alexander, A. M.; Marchi, S.; Chocron, S.; Walker, J.
Abstract: Cratering is a prominent evolutionary process on asteroids. Crater morphologies, regolith generation, bulk fracturing and projectile implantation are all examples of asteroidal surface evolution resulting from impact processes. The characterization of these processes on metal‐rich bodies has become a priority due to the upcoming NASA Psyche mission, poised to study the likely metal‐rich 225‐km main belt asteroid, (16) Psyche. Small‐scale impact experiments into metals (e.g., iron, aluminum, copper, steel) have shown that crater morphologies into these materials are different than rocky targets—exhibiting notable distinctive features such as raised, sharp rims, and deeper cavities. In this work, we determine strength constants for different metals used in prior impact experiments, namely manufactured Fe‐Ni materials and the Gibeon iron meteorite at 77 K. These parameters have been used as inputs for the Johnson and Cook (1983) strength model in a suite of numerical simulations reproducing impact experiments. Using the Johnson and Cook strength model and our laboratory‐derived material constants, we find that it is possible to closely match small‐scale experimental crater diameters and depths using iSALE and CTH shock physics codes. Plain Language Summary: The NASA mission to Asteroid (16) Psyche will launch in 2022. While impact craters are readily observed on rocky and icy bodies throughout the solar system, craters on surfaces made of metal are not as well understood. To best understand and interpret data and observations from the spacecraft at Psyche, cratering experiments have been conducted into centimeter‐sized iron‐nickel cylinders and iron meteorite cubes. In this work, we use numerical modeling to reproduce cratering experiments at the millimeter and centimeter scale to ensure shock physics softwares like iSALE and CTH can be used to explore cratering at the larger scale (meters to kilometers) on metal‐rich surfaces like the asteroid Psyche. Key Points: We conducted several small‐scale 2D numerical shock physics simulations in iSALE and CTH into Fe‐Ni targets We measured material strength parameters via lab tests at quasistatic and high strain‐rates and relevant temperatures for Fe‐Ni materials The simulated craters are average within ∼5% for Fe‐Ni manufactured targets and meteorite cubes, depending on code used